Fermentasi Ekstrak Daun Rambusa (Passiflora Foetida L) pada Pakan untuk Meningkatkan Pertumbuhan Benih Ikan Papuyu (Anabas testudineus) - Sofia Rahmandani; Sri Herlina (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2021)
This study aimed to determine the effect of giving rambusa leaf extract (Passiflora foetida L) to feed with different doses to increase the growth of papuyu fish (Anabas testudineus) fry. Research ii was conducted in April –May 2021. The research method used 4 (four) treatments and 3 (three) replications. The experimental design used was Completely Randomized Design (CRD). The feed given for 42 days of rearing was a mixture of commercial pellets with fermented rambusa leaf extract doses (50 ml, 75 ml, 125 ml and without rambusa leaf extract as a control). Parameters Observation of relative growth rate, feed conversion and survival. The results showed that fermented rambusa leaf extract (Passiflora foetida L) in feed had a significant effect on the relative growth rate, feed conversion (FCR) of papuyu fish (Anabas testudineus) seeds, the optimum dose increased the relative growth rate of 125 mg/kg feed. Keywords : Anabas testudineus, Passiflora foetida L, growth